Interdecadal Variability of Easterly Waves Over the Tropical Northeastern Pacific - V. M. Torres; C. D. Thorncroft (Geophysical Research Letters)
Abstract A time‐series analysis of Easterly Wave (EW) activity, based on dynamical and convective variance measures, was carried out over the tropical northeastern Pacific (EPAC). A significant interdecadal change in EW‐activity was identified shifting from reduced activity in 1980–1997, to increased activity during 1998–2015. The changes in EW‐activity are modulated on interdecadal timescales by the Atlantic Multidecadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO). EW‐activity is increased when there is a positive AMO index and, to a lesser extent, a negative PDO index. The opposite occurred with a negative AMO index and positive PDO index. This relationship can be understood in terms of how the AMO and PDO impact sea surface temperatures (SSTs) in the EPAC. Warmer SSTs tend to be associated with more EW‐related convection and associated vorticity generation in the EW troughs and vice versa. These results suggest potential predictability of EW‐activity in the EPAC on interdecadal timescales.